ANALISIS KESESUAIAN PENGGUNAAN LAHAN PADA DAERAH RAWAN TANAH LONGSOR DI KABUPATEN TEGAL - Gilang Rupaka, Anggun Prima; Suharyanto, Suharyanto; Sudarno, Sudarno (Universitas Diponegoro, 2015)
The frequency of landslides in Tegal regency increasing every year. The distribution area arealso more widespread, especially in districts Jatinegara, Bojong and Bumijawa. These regions has ahilly topography profile with a height ranging from 400 - 1200 meters above sea level. The landslide’sfactors that use as the parameters in this study are rainfall, slope, soil type, depth of soil solum andland use. Suitability of land use based on the level of vulnerability to landslides associated with thelevel of capacity and vulnerability, because the area that not conform based on these factors are theresidential area.The method used to calculate and analyze the landslide-prone area in this study are with thehelp of GIS. The software were used to analyze consist of ArcGIS 10, ER Mapper 7.0 and Basemap.Satellite images digitized with ArcGIS to produce maps of land use. Then the land-use maps overlaidwith maps of slope, soil type maps, rainfall maps and depth of solum. Predefined values for eachparameter were then summed and classified based on assessment standards. The landslidesusceptibility map is then used to analyze the suitability of land in landslide-prone areas in Tegalregency. The level of capacity and vulnerability to disasters in areas prone to landslides obtained byinterview in the form of a questionnaire.Subdistrict Jatinegara, Bojong and Bumijawa has an area of 25.000 hectares, 37,81% of thearea that included in the